2011
DOI: 10.1063/1.3543621
|View full text |Cite
|
Sign up to set email alerts
|

Structural and elemental characterization of high efficiency Cu2ZnSnS4 solar cells

Abstract: We have carried out detailed microstructural studies of phase separation and grain boundary composition in Cu2ZnSnS4 based solar cells. The absorber layer was fabricated by thermal evaporation followed by post high temperature annealing on hot plate. We show that inter-reactions between the bottom molybdenum and the Cu2ZnSnS4, besides triggering the formation of interfacial MoSx, results in the out-diffusion of Cu from the Cu2ZnSnS4 layer. Phase separation of Cu2ZnSnS4 into ZnS and a Cu–Sn–S compound is observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

16
122
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(140 citation statements)
references
References 14 publications
16
122
0
2
Order By: Relevance
“…[1][2][3][4][5][6] Due to the increased number of elements in the materials, their synthesis is relatively more difficult than for binary and ternary semiconductors 7,8 because more secondary phases like ZnS, Cu 2 SnS 3 (CTS), ZnSe and Cu 2 SnSe 3 (CTSe) may coexist in the samples. 9,10 The coexistence of these secondary phase compounds will inevitably influence the electrical and optical properties of CZTS and CZTSe samples, which have been observed experimentally and taken as the reason for the scattering of the measured properties. 11 Despite a long history of the experimental study of CTS and CTSe ternary compounds, their fundamental properties such as the crystal structure and band gap are still under debate.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6] Due to the increased number of elements in the materials, their synthesis is relatively more difficult than for binary and ternary semiconductors 7,8 because more secondary phases like ZnS, Cu 2 SnS 3 (CTS), ZnSe and Cu 2 SnSe 3 (CTSe) may coexist in the samples. 9,10 The coexistence of these secondary phase compounds will inevitably influence the electrical and optical properties of CZTS and CZTSe samples, which have been observed experimentally and taken as the reason for the scattering of the measured properties. 11 Despite a long history of the experimental study of CTS and CTSe ternary compounds, their fundamental properties such as the crystal structure and band gap are still under debate.…”
mentioning
confidence: 99%
“…Существует несколько способов получения пленок данных материалов, основные из них: вакуумное ис-парение [2,3], соиспарение [4,5], золь-гель метод [6,7] и электроосаждение [8]. Достаточно успешный подход, основанный на спин-коутинге из раствора частиц в гидразине, был предложен компанией IBM для изго-товления фотоэлектрических устройств с КПД более 11.1% на основе Cu 2 ZnSn(S,Se) 4 [6].…”
Section: Introductionunclassified
“…Однако, несмотря на перспективу этих технологий, относительно небольшая распространен-ность в природе In и Те ограничивает производственные мощности для батарей на их основе по прогнозам до < 100 GWP в год. Более низкая стоимость руд, содержащих медь, цинк или олово -основу кестеритов Cu 2 ZnSn(S,Se) 4 (CZTSe) -делает их привлекательной альтернативой для CdTe или CIGS.Существует несколько способов получения пленок данных материалов, основные из них: вакуумное ис-парение [2,3], соиспарение [4,5], золь-гель метод [6,7] и электроосаждение [8]. Достаточно успешный подход, основанный на спин-коутинге из раствора частиц в гидразине, был предложен компанией IBM для изго-товления фотоэлектрических устройств с КПД более 11.1% на основе Cu 2 ZnSn(S,Se) 4 [6].…”
unclassified
“…Using secondary ion mass spectrometry (SIMS), Mousel et al [20] detected a Sn-enrichment at the surface of the annealed precursor, which suggested the formation of a Cu-Sn-Se compound, whereas Wang et al [24] detected Cu-Sn-S compounds at the CZTS/ Mo interface by EDX.…”
Section: Introductionmentioning
confidence: 99%
“…Mousel et al [20] and Wang et al [24] prepared precursors by a low temperature (320 C and 110 C, respectively) co-evaporation process and applied a post-deposition annealing process in a SnSe þ Se atmosphere and in a S atmosphere, respectively. Using secondary ion mass spectrometry (SIMS), Mousel et al [20] detected a Sn-enrichment at the surface of the annealed precursor, which suggested the formation of a Cu-Sn-Se compound, whereas Wang et al [24] detected Cu-Sn-S compounds at the CZTS/ Mo interface by EDX.…”
Section: Introductionmentioning
confidence: 99%